Short story writing experiences and perceptions of Saudi female university students - Saaty, Ahdab Abdalelah (Journal of International Students, 2025)
This study investigates how writing short stories can be integrated into the curriculum of teaching English as a foreign language (EFL) to consolidate students’ knowledge of the language and promote their creative writing skills. It aims to understand students’ experiences writing fiction and nonfiction short stories. Data were obtained from students’ short stories written electronically during an English course and their responses to a post-task questionnaire. A mixed-method explanatory sequential research approach was adopted. Qualitative and quantitative data were derived from the themes explored and descriptive statistics of the short stories written by the participants. Qualitative data were obtained from students’ perceptions gauged from their post-task questionnaire responses. The findings indicate that writing short stories effectively reinforced students’ prior English knowledge and encouraged creative and imaginative writing while breaking the monotony of typical classroom procedures.